Photochemical electron transfer between methylene blue and quinones - Misni, M.; Dennis, M.; Peter, V.; Alex, H. (1994)
Methylene Blue is a well known photochemical oxidant. In this paper we present results of cyclic voltammetry and laser flash photolysis experiments which demonstrate that Methylene Blue may function also as a photochemical reductant. Laser flash photolysis studies of Methylene Blue were carried out in aqueous solution at pH 10, in ethanol and in aqueous dispersions of lipid vesicles in the presence of benzoquinol, benzoquinone and the long-chain naphthoquinone Vitamin K1. Both the quinones and the quinol affected the transient of the decay of triplet Methylene Blue to its ground electronic state. The transients were biphasic and characteristic of an initial electron transfer reaction between triplet Methylene Blue and the quinone or quinol, followed by back electron transfer between the products. For Vitamin K1 and Methylene Blue in ethanol the back electron transfer was very slow (lifetime about 4 ms). This slow back electron transfer is favourable to the use of this system for energy storage via photosynthetic solar energy conversion.